Carbon Fiber Composites for Large-Scale Wind Turbine Blades: Applicability Study and Comprehensive Evaluation in China - Hanwei Teng; Shujian Li; Zheng Cao; Shuang Li; Changping Li; Tae Jo Ko (Journal of Marine Science and Engineering, 2023)
Wind energy is a type of clean energy that can address global energy shortages and environmental issues. Wind turbine blades are a critical component in capturing wind energy. Carbon fiber composites have been widely recognized for their excellent overall performance in large-scale wind turbine blades. However, in China, the wide application of carbon fiber composites in wind turbine blades still faces many problems and challenges. This paper examines the current state of carbon fiber composites for wind turbine blades and the geographical distribution characteristics of wind resources in China. The economic revenues from increasing the length of wind turbine blades in four typical wind farms, including offshore wind farms, are compared. Using a mathematical model, the energy efficiency of carbon fiber composites in the application of large wind turbine blades is evaluated from the aspects of cost, embedded energy, and carbon footprint. Further, the current relationship between supply and demand for the industrial structure of carbon fiber in China is revealed. The manufacturing technologies for carbon fiber composite wind turbine blades are analyzed, and corresponding countermeasures are proposed. Finally, the incentive policy for applying carbon fiber composites to wind turbine blades is explained, and the development prospects are explored. In this paper, the economics and energy efficiency of the application of carbon fiber composite materials in large wind turbine blades are analyzed and comprehensively evaluated by using mathematical models, which will provide a valuable reference for China’s wind turbine blade industry.